Image processing based analysis of moving shadow effects for reconfiguration in PV arrays - Karakose, Mehmet; Baygin, Mehmet (IEEE Computer Society, 2014)
Reconfiguration process is very important in terms of efficiency in photovoltaic (PV) arrays under especially in partial shading conditions. Although there are some studies for reconfiguration process in the literature, they are difficult and complex. In this study, full or partial shading effects on arrays are examined and presented for reconfiguration of PV arrays. System performance is intended to increase by making image-processing based moving shadow analysis. Reconfiguration of PV arrays is provided with proposed approach under the partial shading conditions without information of current (I), voltage (V) and power (P) which is quite difficult to measure. Experimental results are verified by using a video image obtained from a real PV array and effective results are obtained. © 2014 IEEE.
2014 IEEE International Energy Conference, ENERGYCON 2014 -- 13 May 2014 through 16 May 2014 -- Dubrovnik -- 106639
Keywords: Image Processing; Moving Shadow Detection; Partial Shading; Photovoltaic Systems; Reconfiguration